PENERAPAN STRATEGI REACT DENGAN MEDIA VISUAL DALAM PENINGKATAN HASIL BELAJAR IPS TENTANG KOPERASI PADA SISWA KELAS VI SDN 3 PANJER TAHUN AJARAN 2015/2016 - Pratiwi, Ika Serfiani (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of REACT Strategy Using Visual Media in Improving Social Science Learning Outcomes about Cooperation for the Fourth Grade Students of SD Negeri 3 Panjer. The objective of this research is to improve social science learning outcomes about cooperation for the fourth grade of SD Negeri 3 Panjer through the implementation of REACT using visual media. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles through stages: planning, action, observation, and reflection. Subjects of the research were fourth grade students of SD Negeri 3 Panjer totaling 22 students. Techniques of collecting data were learning outcomes test, observation, and interview. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. The result of this research showed that the implementation of REACT strategy using visual media can improve social science learning outcomes for the fourth grade students of elementary schools. It was proved by the increase of learning mastery percentage in the first cycle 72.73%, in the second cycle 81.82%, and in the third cycle 90.91%. Keywords: REACT strategy, visual media, learning outcomes, social science Abstrak: Penerapan Strategi REACT dengan Media Visual dalam Peningkatan Hasil Belajar IPS tentang Koperasi pada Siswa Kelas IV SDN 3 Panjer. Penelitian ini bertujuan untuk meningkatkan hasil belajar IPS siswa kelas IV SD melalui penerapan strategi REACT dengan media visual. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus dengan tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa IV SDN 3 Panjer dengan 22 siswa. Data penelitian ini berasal dari guru dan siswa. Teknik pengumpulan data dalam penelitian ini menggunakan observasi, wawancara, dan tes. Validitas data dalam penelitian ini menggunakan teknik triangulasi sumber dan triangulasi teknik. Hasil penelitian ini menunjukkan bahwa strategi REACT dengan media visual dapat meningkatkan hasil belajar IPS siswa kelas IV SD. Persentase ketuntasan hasil belajar siswa yang diperoleh pada siklus I mencapai 72,73%, siklus II mencapai 81,82%, dan siklus III mencapai 90,91%. Kata Kunci: Strategi REACT, Media Visual, Hasil Belajar, IPS